30 | Clinical care pathways for the management of time-critical conditions - F. Lotito; A. Sarcone; V. Bosco; G. M. Medici; A. Gallucci (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2026)
Background. The Provincial Health Authority of Catanzaro implemented two Clinical Care Pathways (CCPs) aimed at standardizing the management of two time-critical conditions: pulmonary embolism and hip fracture in patients aged ≥65 years. These are high-risk clinical conditions in which patient outcomes, including survival and functional recovery, are closely related to the timeliness of therapeutic intervention. Materials and Methods. The Hip Fracture Clinical Care Pathway (Resolution No. 1337/2023) targets patients aged 65 years or older and aims to ensure surgical treatment within 48 hours of hospital admission, in accordance with the quality standards established by the Italian Ministerial Decree (DM 70/2015), which sets a minimum target of 60% of eligible cases. The pathway standardizes the entire clinical process, from emergency department admission and multidisciplinary assessment (orthopedic surgeon, anesthesiologist, and cardiologist) to postoperative management and rehabilitation planning. Outpatient follow-up is scheduled 30 days after hospital discharge. The Pulmonary Embolism Clinical Care Pathway (Resolution No. 920/2024), developed in accordance with Calabria Regional Decree No. 122/2019 and based on the 2022 ESC/ERS Guidelines, defines the management of patients presenting to the emergency department with suspected pulmonary embolism. Two clinical scenarios are identified: hemodynamically unstable patients (Scenario A), who have an estimated early mortality of approximately 30% and may be eligible for systemic thrombolysis with recombinant tissue plasminogen activator (rtPA), and hemodynamically stable patients (Scenario B). Direct oral anticoagulants (DOACs) are recommended as the first-line anticoagulant therapy when appropriate. Prognostic risk stratification using the Pulmonary Embolism Severity Index (PESI) guides decisions regarding hospital admission or early protected discharge. Results. Following implementation of the clinical care pathways, annual monitoring of hospital quality indicators demonstrated a substantial improvement in healthcare performance measures. Conclusions. Both clinical care pathways promote a multidisciplinary approach, reduce diagnostic and therapeutic delays, and enhance continuity of care, thereby contributing to